International Children's Continence Society standardization report on urodynamic studies of the lower urinary tract in children. Issue 7 (21st May 2015) - Bauer, Stuart B.; Nijman, Rien J.M.; Drzewiecki, Beth A.; Sillen, Ulla; Hoebeke, Piet
<x xml:space="preserve">Abstract</x> Aims The objective of this document created by the ICCS standardization subcommittee is to provide a uniform guideline on measurement, quality control and documentation of urodynamic studies in children. Methods This guideline was created using expert opinion and critical review of the published literature on urodynamic studies in children. Currently no standardized guideline or level 1 data exists on the proper technique for this subject matter. Results The document provides a throughout explanation on how to approach a child who presents with lower urinary tract dysfunction, whether it be of neurogenic, anatomic or functional origin. Formation of an urodynamic question after a comprehensive history and physical examination is paramount in selecting the urodynamic study(ies) that will be most appropriate for each child. Appropriate application of each test with careful consideration of the needs of the child and family will provide the most accurate and reproducible results. Recommendations on how to execute each of the components of an urodynamic study as well as interpretation are included in the document. Conclusions Urodynamic studies have become a major tool in evaluating lower urinary tract dysfunction in children. There are many subtleties in performing these studies in children in juxtaposition to adults; therefore, adaptations specific to children must be made to achieve accurate and reproducible results. Uniformity in how the studies are conducted from center to center will allow for healthier transparency and enhanced comparison of results in both clinical and research situations. Neurourol. Urodynam. 34:???–???, 2015. © 2015 Wiley Periodicals, Inc.